The norovirus features, detection and prevention of foodborne disease - Chan, Paul K. S.; Guan, Haishan; Chan, Martin C. W. (Academic Press, 2017)
The Norovirus: Features, Detection and Prevention of Foodborne Disease is a unique and valuable reference for both researchers in industry and students who need to understand how this specific pathogen behaves in order to improve control of food as a transmission of this infectious biological agent. The information in the book provides essential, specific information to help further understand potential new strains of the pathogen, offering detection analysis and prevention strategies of the pathogen to assist in combatting the spread of foodborne illness. Written by national and international experts in the field, this book will be a practical source of information for food scientists, food microbiologists, food technologists, food industry workers, public health workers, and students
Includes bibliographical references and index
Keywords: MEDICAL / Gastroenterology; Foodborne diseases / Prevention; Virus diseases / Prevention; Norovirus; Viral gastroenteritis -- Prevention; Virus diseases -- Prevention; Foodborne diseases -- Prevention